Seleksi Galur Kedelai (Glycine Max (L.) Merril) Generasi F4 Pada Tanah Salin - Zulfi Agus Leonard Sitepu; Rosmayati Rosmayati; Isman Nuriadi (Jurnal Agroekoteknologi, 2014)
Strain Selection of Soybean (Glycine max (L)Merril) of F4 Generation on Saline Soil. This researchaims to select the soybeans that can grow well and good production on saline soil of F4 generation.This research was conducted at Tanjung Rejo village,subdistrict of Percut Sei Tuan, Regenecy ofDeli Serdang,the elevation is 1.5m on above sea level,since November 2012 up to January 2013.The analysis used in this research is fingerprint analysis of cross that consist of 1 variety, themethod applied is a F4 generation pedigree selection,the population is sample, number of live plantis 43 of 690. The selected plant is based on the grain production per plant for 30 plants.Based on theresults of research that based on the highest weight of seed per plant is 1.4g on the plant number514.1.8.6 and the lowest production is 0.1g on the plant number 88.5.10.2, 1298.5.3.1, 1298.5.3.30,1298.5.3.40, 1298.5.7.16 and 1298.5.7.25. The components of production that has a direct influenceto the grain production per plant are the number of branch,age of flowering,number of pod andnumber of pods contain. Component of production that giving the highest direct influence is thenumber of pod contain for 8.809.Keyword : Species, Soybean, Selection, Salinity.